Effect Extract Rosella (Hibiscussabdariffa) As An Alternative To Natural Tooth Bleaching Agent On External Discoloration Case - Nanik Sugianti (Universitas Muhammadiyah Yogyakarta, 2012)
Tooth bleaching is one effort that has long been known in the science of dentistry. Unfortunately material used to whiten tooth until now they are still nature are toxic to tissues of the mouth cavity. Whereas with traditional natural materials exploration in Indonesia, give all one plant used as a safe teeth bleaching, rosella (Hibiscus sabdariffa). The research to find out effect extract rosella (Hibiscus sabdariffa) to external discoloration. Methods: An experimental research with Pre and Post Controlled Group Design. The sample consist of 12 teeth which divided into two groups. The first group, as control, were soaked in aquadest and the second group, as treatment were soaked in extract rosella (Hibiscus sabdariffa) for 3 days. Colour analysis is conductedbyCIELAB method. The colected data were analized by Pairing t-test. Discussion: Rosella (Hibiscus sabdariffa) containing bioactive compounds, saponins that foam can bind colourants. With the power of his work which can bind the colourants can be used to whiten teeth. In addition, vitamin C (Ascorbic acid) that high can cause email erosion. The compound is capable of damaging colour substance molecules become neutral color so that the color and causing bleaching effects. Conclusion: Rosella (Hibiscus sabdariffa) can be used as an alternative natural tooth bleaching agent because it contains the active agent of saponin and vitamin C are high.